2016
DOI: 10.1007/s12325-016-0423-5
|View full text |Cite
|
Sign up to set email alerts
|

α1-Blockers in Men with Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Obstruction: Is Silodosin Different?

Abstract: Available α1-blockers (ABs) have different profiles of receptor selectivity. Silodosin exhibits the highest selectivity for the α1A adrenergic receptor. This pharmacological feature couples with a singular urodynamic and clinical profile. The magnitude of bladder outlet obstruction improvement in patients receiving silodosin is higher if compared to other ABs. From a clinical point of view, current evidence suggests an advantage in favor of silodosin in terms of nocturia improvement and cardiovascular safety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The main rationale for treatment of nocturia with selective α 1 -adrenoceptor (AR) antagonists is that the drugs have a documented effect in the treatment of LUTS, including nocturia [ 29 ]. However, the precise mechanism behind their effect on nocturia is yet to be elucidated.…”
Section: Drug Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main rationale for treatment of nocturia with selective α 1 -adrenoceptor (AR) antagonists is that the drugs have a documented effect in the treatment of LUTS, including nocturia [ 29 ]. However, the precise mechanism behind their effect on nocturia is yet to be elucidated.…”
Section: Drug Alternativesmentioning
confidence: 99%
“…Kim et al [ 31 ] investigated improvement in nocturia and nocturnal polyuria after silodosin administration by using a 3-day frequency–volume chart in a prospective multicenter study and found a significant reduction of nocturnal urine volume at 12 weeks compared to screening ( p = 0.001). Roehrborn et al [ 29 ] not only hypothesized that reduction of nocturnal polyuria combined with improved functional bladder capacity are potential mechanisms of action of α 1 -AR antagonists on nocturia, but also that this effect it is related to α 1 -AR subtype selectivity as none of the individual α 1 -AR antagonists without subtype selectivity has consistently shown a significant reduction in nocturnal voiding episodes [ 33 ]. A multicenter 12-wk trial randomized men to receive silodosin, tamsulosin, or placebo and found that only silodosin significantly reduced nocturia versus placebo ( p = 0.013) and the change from baseline was − 0.9, − 0.8, and − 0.7 for silodosin, tamsulosin, and placebo, respectively [ 34 ].…”
Section: Drug Alternativesmentioning
confidence: 99%
“…Reportedly, ureteral smooth muscle α1-ARs are denser than other adrenoceptors, and a homogeneous distribution of different α1-AR subtypes has been noted in the human ureter [ 7 ]. In several clinical reports, α1-AR antagonists, including alfuzosin, doxazosin, tamsulosin, silodosin, and naftopidil, were shown to inhibit ureteral contraction [ 8 9 ]. Based on the findings of a randomized controlled study, α1-AR antagonists can be used to promote the spontaneous excretion of ureteral stones in patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that SLD has higher selectivity for the dominant subtype of the α1A-adrenergic receptor in prostate tissues and inhibits the contraction of prostate smooth muscle. Therefore, it is widely used clinically in the treatment of BHP (Marks, Gittelman, Hill, Volinn, & Hoel, 2009;Roehrborn, Cruz, & Fusco, 2017;Yoshida et al, 2011). The use of the Analytical Quality by Design (AQbD) approach during the development of a new analytical method is an effective strategy in terms of time and quality (Kurmi, Singh, Bhutani, Singh, & Beg, 2014;Peraman, Bhadraya, & Reddy, 2015).…”
Section: Introductionmentioning
confidence: 99%